Applications of identity-based theories to understand the impact of stigma and camouflaging on mental health outcomes for autistic people - Rivera, Rachel A.; Bennetto, Loisa (Frontiers in Psychiatry, 2023)
Autistic people have long been conceptualized from a deficit-based model of disability, but recent self-advocates and scholars have asserted the importance of recognizing autism as both a disability and an important part of a person's social identity. The autistic identity is subject to specific stigma and stressors beyond everyday discrimination and prejudice, which can have many downstream implications on mental health and well-being. Prior research on camouflaging has explained both quantitatively and qualitatively how autistic people conform to norms and mask their autistic traits to better fit in with non-autistic societal standards. Given this paradigm shift in understanding autistic peoples' lived experiences, researchers must also begin to reshape the theories guiding their work in order to improve diagnosis, intervention, and supports. This review examines the extant research on identity-related stigma and camouflaging and their subsequent impacts on mental health outcomes in autism. A model is proposed integrating identity-based theories-specifically the social model of disability, social identity theory, and minority stress model-to explain relationships across research areas and better explain the experiences of autistic people. We discuss how identity-based theories can be applied in autism research to better understand the impacts of stigma and camouflaging on autistic peoples' lived experiences and reduce disparities in their mental health outcomes.